Ideal Islamic Educational Organizational Culture - Jaudi, Jaudi (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Organizational culture plays a significant role in success, especially in Islamic education, where integration of shared values ​​and adaptation to external changes are challenges. Organizational culture also influences individual and group performance assessments. This study aims to examine how leaders can build shared meaning that strengthens organizational culture and explains the effective socialization process for members in facing rapid change. The method used is a qualitative approach with a literature study model, where data is collected from various relevant literature and documents on organizational culture and analyzed using content analysis techniques to identify emerging themes and patterns. The results of the study indicate that a strong organizational culture is closely related to effective leadership and the importance of the socialization process in shaping organizational identity. There is a dynamic interaction between togetherness and adaptation in overcoming internal and external challenges. This study provides an understanding of organizational culture, especially in the context of Islamic education, and provides a more comprehensive framework for management in facing change and increasing organizational effectiveness.